Respon Pertumbuhan Anggrek Hitam (Coelogyne pandurata Lindl.) Secara In-Vitro dengan Penambahan Ekstrak Taoge Dan Benzyl Amino Purine (BAP) - Riza Linda, Winda Saputri, Mukarlina, (Jurnal Protobiont, 2015)
Black orchid (Coelogyne pandurata Lindl.) is the one type of orchid that spread to Sumatera and Kalimantan. This species of orchid is sought-after because of its potentially high economic value, so it has often been excessively exploited but not widely cultivated. This research aimed to reveal the influence ofthe extracts of bean sprout and benzyl amino purine (BAP) for the growth of the black orchid (C. pandurata). The research was conducted from May to December 2014 at the Laboratory of Tissue Culture, Department of Biologyand the Aloe Vera Center Pontianak. The experimental design used was the completely randomized design (CRD) with 2 treatment level. The first level was extract of bean sprout (0%; 5%; 7.5%; 10%) and second level BAP (0 ppm; 5 ppm; 7.5 ppm; 10 ppm). The results of the research revealed that the shoots appeared the fastest at the combined treatment of 10% bean sprout extract and 10ppm BAP, i.e. 5.38 days. The number of shoots appearred most at the treatment of 10% bean sprout extract and 10 ppm BAP with shoots appearing at an average of 3.79 ppm. The addition of 5% bean sprout extract resulted in the highest average number of leaves i.e. 3.77.